Análisis del impacto de las cuentas por cobrar de los clientes de la cooperativa “Guaranda ltda” en el cantón caluma durante el periodo 2020. - Rubio Leal, Rosalinda Stefania (2022)
The study generated with the title "ANALYSIS OF THE IMPACT OF THE ACCOUNTS RECEIVABLE OF THE CUSTOMERS OF THE COOPERATIVE "GUARANDA LTDA" IN THE CALUMA CANTON DURING THE 2020 PERIOD" executes an analysis of the accounts receivable that the institution has based on the default that occurs on the part of the clients with the financial institution, the same one that developed several problems that became a weight for the administration and managers of the place, having to create a series of activities that would allow generating a change within the payment culture by customers, to obtain a prompt solution. The evaluation of the accounts receivable of the entity consisted of a case that may present an interest, where possible activities can be determined to be applied in the long term and that serve the increase in addition to the clients within the entity. The applied methodology consists of an exploratory analysis method, where it is sought to detect individual problems to reach a generalized conclusion that allows obtaining answers that are truthful and that help to comply with the formulation of the conclusions. As results and conclusion of the work, evidence was generated that proves that the accounts receivable of the company have presented an increase, where they maintain a high weight on the total assets, representing more than 50% of all the assets that are owned of Guaranda Ltda.